Fine art and high finance expert advice on the economics of ownership - McAndrew, Clare. (Bloomberg Press, 2010)
"Art investors and collectors can't protect and profit from their collections without grappling with a range of complex financial issues like risk, insurance, restoration, and conservation. In Fine Art and High Finance, Clare McAndrew and a highly qualified team of contributors explain the most difficult financial matters facing art investors"--Provided by publisher.